Microsoft FoxPro : relational database management system. (Apple Macintosh series., 1993)
Relational database management system for the Macintosh. Enables developers to create applications that can be ported to another platform. Supports Apple Events, TrueType fonts, QuickTime, and ability to call XCommands and XFunctions. Supports OLE 1.0 (object linking and embedding) and FileMaker Pro data.